Bilevel optimization for the deployment of refuelling stations for electric vehicles on road networks - Piedra-de-la-Cuadra, Ramón; Ortega, Francisco A. (Computers & operations research, 2024)
This work consists of a procedure to optimally select, among a group of candidate sites where gas stations were already located, a sufficient number of charging points in order to guarantee that an electric vehicle can make its journey without a problem of energy autonomy and that each selected charging station has another one that serves as useful support in case of failure (reinforced coverage service). For this purpose, we propose a bilevel model that, in a former level, minimizes the number of refuelling points necessary to guarantee a reinforced service coverage for all users who transit from their origin to destination and, as a second level, maximize the volume of demand that can be satisfied subject to budgetary restrictions. With the first of the objectives we are addressing the typical requirement of the administration, which consists of guaranteeing the viability of the solutions, and the second of the objectives is a criterion typically used by the private sector initiative, compatible with the profit maximization. •Two models for the transformation of gas stations into electric stations.•Each model with distinct priorities: coverage optimization and node attractiveness.•Computational experiments consider instances with a larger number of gas stations.•Heuristic H generates intermediate solutions between the exacts solutions.